Air change rates in urban Chinese bedrooms. (10th July 2019) - Hou, Jing; Sun, Yuexia; Chen, Qingyan; Cheng, Rongsai; Liu, Junjie; Shen, Xiong; Tan, Hongwei; Yin, Haiguo; Huang, Kailiang; Gao, Yao; Dai, Xilei; Zhang, Leiming; et al.
Abstract: The ventilation modalities in most Chinese residences are infiltration and opening windows. We measured infiltration rates and air change rates at night, with no attempt to change occupants' behaviors, of urban residences in five climate zones of China during four seasons. Using the CO2 decay method, we found the median infiltration rate for 294 residences to be 0.34 h −1 . Using occupant‐generated CO2 as tracer gas, we determined air change rates over the course of 1 year in 46 bedrooms at night from mass balance considerations. In 54% of the measurements, windows were closed, so ventilation was only by infiltration. Windows were mainly closed when the outdoor temperature was below 15°C and above 26°C. The median infiltration rates did not differ appreciably among seasons and climate zones and were always less than 0.45 h −1 .